2014
DOI: 10.1007/s11552-014-9669-z
|View full text |Cite
|
Sign up to set email alerts
|

Barbed Sutures and Tendon Repair—a Review

Abstract: Introduction Traumatic tendon lacerations are a common problem encountered by hand surgeons worldwide. Although the use of barbed suture to repair tendon lacerations has gained theoretical popularity in recent years, there is little information available regarding the safety, efficacy, longevity, or complications encountered when used in tenorraphy. In this study, we review the available literature on the use of barbed suture in tendon repair. Methods Studies conducted between 1980 and 2014 were identified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…However, both fabrics indicated stress levels that are consistent with the stress levels of real tendons [29][30][31], indicating that the contact pressure due to the braided fabric could be within the limits of tendon stresses.…”
Section: Parameter Study Of Tendon Repair With Regular-braided Fabricsupporting
confidence: 55%
“…However, both fabrics indicated stress levels that are consistent with the stress levels of real tendons [29][30][31], indicating that the contact pressure due to the braided fabric could be within the limits of tendon stresses.…”
Section: Parameter Study Of Tendon Repair With Regular-braided Fabricsupporting
confidence: 55%
“…The stitch is passed into the tissue in the opposite direction to the splay of the barb, allowing the suture to pass easily. When a force is applied in the opposite direction, the barb of the suture grasps the surrounding tissue and secures the tissue in place 16 . A continuous knotless suture can immediately provide excellent waterproof tightness, reducing saliva infiltration between tissues of different thickness and type.…”
Section: Discussionmentioning
confidence: 99%
“…5 Since then, multiple improvements have been made to this barbed suture technology and their use has been widely applied to various fields including plastic, urological, and general surgery, as well as obstetrics/gynecology, and orthopedics. [6][7][8] Preclinical and biomechanical studies have demonstrated effectiveness in cosmetic skin and deep tissue closures. In addition, barbed sutures have been shown to provide watertight closure and wound strength comparable to or superior to closure with conventional sutures.…”
mentioning
confidence: 99%